POD, CAT and SOD enzyme activity of corn kernels as affected by low plasma pretreatment - Xing Jin; Zhe Liu; Wenfu Wu (International Journal of Food Properties)
In this study, low-temperature plasma was used as an efficient pretreatment method of corn kernels (XY335), which developed and optimized a process of enzyme activity. The effects of plasma pretreatment power (300, 400, 500 W), plasma pretreatment time (30, 40, 50 s) and air flow rate (100, 150, 200 mL min−1) on enzyme activity during this process were investigated. Regression equations were established through a three-factor and three-level Box-Behnken design and used to evaluate the optimal conditions for the process. The optimal pretreatment conditions of POD enzyme activity were plasma pretreatment power of 500 W, plasma pretreatment time of 30 s and air flow rate of 150 mL min−1. The optimal pretreatment conditions of CAT enzyme activity were plasma pretreatment power of 350 W, plasma pretreatment time of 30 s and air flow rate of 150 mL min−1. The optimal pretreatment conditions of SOD enzyme activity were plasma pretreatment power of 400 W, plasma pretreatment time of 30 s and air flow rate of 200 mL min−1. Results showed that low-temperature plasma can be used effectively to increase the enzyme activity of corn kernels.